2018
DOI: 10.1155/2018/5489215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chailong Jieyu Pill on Behavior, Monoamine Neurotransmitters, and Corticosteroid Receptors in a Rat Model of Anxiety Disorder

Abstract: Chailong Jieyu Pill (CJP) is composed of Radix Bupleuri, Radix Scutellariae, Rhizoma Pinelliae Preparata, Radix Codonopsis, Radix Glycyrrhizae preparata, keel, Concha Ostreae, Concha Margaritifera Usta, Rhizoma Zingiberis Recens, and Fructus Jujubae. CJP has shown good clinical effects on improving anxiety disorders. However, as the mechanism underlying such benefits remains unclear, the aim of this study was to investigate the mechanism of action for CJP on anxiety-related behaviors in a rat model of anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…81,82 In the in vivo study, the levels of DA and 5-HT in the serum, hippocampus, mPFC, and amygdala of mice in the anxious state were higher than those of the control mice. These results are in agreement with several studies on different anxiety models, which confirmed elevated 5-HT and DA levels 83 EPM, 84 and uncertain empty bottle stimulation 85 induced anxious rodents. In addition, in vivo data demonstrated that this abnormal increase in 5-HT and DA levels was restored after treatment with RC extract, validating the predicted important role of dopaminergic synapses and serotonergic synapses in C. chinensis Franch.…”
Section: Discussionsupporting
confidence: 93%
“…81,82 In the in vivo study, the levels of DA and 5-HT in the serum, hippocampus, mPFC, and amygdala of mice in the anxious state were higher than those of the control mice. These results are in agreement with several studies on different anxiety models, which confirmed elevated 5-HT and DA levels 83 EPM, 84 and uncertain empty bottle stimulation 85 induced anxious rodents. In addition, in vivo data demonstrated that this abnormal increase in 5-HT and DA levels was restored after treatment with RC extract, validating the predicted important role of dopaminergic synapses and serotonergic synapses in C. chinensis Franch.…”
Section: Discussionsupporting
confidence: 93%
“…For understanding the mechanism of action of a TCM formula at the systems level, it is essential to integrate the molecular mechanism into the system-wide mechanism of action. The representative TCM formulas in depression treatment are, but no limited to, Xiao-Yao-San (Chen et al, 2008), Kai-Xin-San (Fu et al, 2020), Jie-Yu-Wan (Feng et al, 2018), Shu-Yu-San (Chen et al, 2012), Chaihu-Jia-Longgu-Muli-Tang (Li et al, 2011), and so on. CUMS, chronic unpredictable mild stress; CSDS, chronic social defeat stress; CMS, chronic mild stress; SDM, social defeat model; CORT, corticosterone; CUS, chronic unpredictable stress; WKT, Wistar Kyoto; LPS, lipopolysaccharides.…”
Section: The Hpa Axismentioning
confidence: 99%
“…In addition, people with poor physique often have a longer course of disease. In fact, the stagnation of liver-Qi and stagnation of Qi are crucial for the onset of this disease [ 6 ]. Thus, in TCM, the stagnation of the liver-Qi syndrome type and liver stagnation transforming into the fire type are common.…”
Section: Introductionmentioning
confidence: 99%